2023
DOI: 10.1002/phar.2866
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of risdiplam in spinal muscular atrophy: A systematic review and meta‐analysis

Carlos Pascual‐Morena,
Vicente Martínez‐Vizcaíno,
Iván Cavero‐Redondo
et al.

Abstract: ObjectivesThis systematic review and meta‐analysis aimed to assess the efficacy and safety of risdiplam on motor and respiratory function in spinal muscular atrophy (SMA).MethodsWe systematically searched Medline, Scopus, Web of Science, and the Cochrane Library from inception to March 2023. We included pre‐post studies that determined the effect of risdiplam on the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP‐INTEND), the 32‐item Motor Function Measure (MFM32), the Revised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“… 81 A more recent publication of a systematic review and metanalysis study reported that after 12 months of treatment with risdiplam, 57% of participants with SMA type 1 achieved a CHOP-INTEND score ≥ 40 points, and more than half were able to feed orally and had head control. 85 In SMA types 2 and 3, MFM32, RULM, and HFMSE increased by 2.09, 1.73, and 1.00 points, respectively. 85 …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“… 81 A more recent publication of a systematic review and metanalysis study reported that after 12 months of treatment with risdiplam, 57% of participants with SMA type 1 achieved a CHOP-INTEND score ≥ 40 points, and more than half were able to feed orally and had head control. 85 In SMA types 2 and 3, MFM32, RULM, and HFMSE increased by 2.09, 1.73, and 1.00 points, respectively. 85 …”
Section: Resultsmentioning
confidence: 90%
“… 85 In SMA types 2 and 3, MFM32, RULM, and HFMSE increased by 2.09, 1.73, and 1.00 points, respectively. 85 …”
Section: Resultsmentioning
confidence: 90%
“…In a monocentric longitudinal cohort study, HFMSE and Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) scores increased in parallel with increases of CMAP amplitudes in both median nerves in 18 adult patients with SMA type 2 or 3 treated with risdiplam during a 10-month treatment period [ 23 ]. Observational studies, meta-analysis and real life will likely define its therapeutic effect in adult patients [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Real-world experience with risdiplam has also been published and further supported its beneficial effects on motor function in patients with SMA. 49 RAINBOWFISH is an ongoing, multicenter, open-label, single-arm study to assess the efficacy and safety of risdiplam in pre-symptomatic SMA. Preliminary data showed that most infants treated with risdiplam could sit independently, and many were standing and walking as assessed by the HINE-2 at month 12.…”
Section: Sod1-alsmentioning
confidence: 99%
“… 48 Real-world experience with risdiplam has also been published and further supported its beneficial effects on motor function in patients with SMA. 49 …”
Section: Spinal Muscular Atrophy Linked To 5q (Sma-5q)mentioning
confidence: 99%